Prežihov Voranc in avstrijska Koroška ali O težavah s Prežihom - Leben, Andrej (Jezik in slovstvo, 2010)
The article provides a description of Prežih´s connection with Austrian Carinthia and his striving for the political unification of Carinthian Slovenes, who were separeted by the new Yugoslav-Austrian border after the result of the 1920 referendum. It sheds light on the characteristics and problems related to the mediation of Prežih and his literature in Austrian Carinthia after the Second World War. Particular attention is devoted to Prežih´s reception and popularisation on the strength of his theatre activities. This strongly markes his image amongst the Slovene Carinthian public, while until recently he remained almost entirely unknown to his German speaking compatriots.
Keywords: Prežihov, Voranc; Slovene literature; slovenska književnost; slovenski pisatelji; avstrijska Koroška; Carinthia; Carinthian Slovenes; koroški Slovenci; Carinthian Plebiscite; koroški plebiscit; politics; politika; ideologija; gledališka dejavnost; 1. pol. 20. st.